Unveiling the Role of Social Determinants in Shaping Health Trajectories for Children and Adults with Congenital Heart Disease: A Systematic Review - Khan, Javeria Khalid; Fatima, Saiyida Kaunain; Siddiqui, Shoaib; Alwaaz, Alwaaz; Khalil, Saima; Maqsood, Syed Uzair; Shams, Amber (Journal of Neonatal Surgery, 2025)
Congenital heart disease (CHD) is one of the most common birth defects worldwide, affecting children and adults alike. Although medical care advances have led to better outcomes, disparities in care continue, driven largely by social determinants of health (SDH). The goal of this review is to summarize data and generate future research directions about the contribution of SDH in defining the health trajectory of individuals with CHD throughout the lifespan. We investigate subtheme areas of SES, geographic access to care, racial/ethnic disparities, education, family support, and healthcare system navigation to inform policy, practice, and health equity interventions